Low Test Scores in Latin America: Poor Schools, Poor Families, or Something Else? (2016)
Latin American students consistently score low on international tests of cognitive skills. In the PISA 2012 results, students in seven Latin American countries had an average score of 395, or about 100 points lower than the average score of 497 in four Scandinavian countries. We examine why Latin American scores are lower and conclude that 50 points are explained by Latin American families’ lower average educational and socioeconomic characteristics, 25 points are explained by Latin America’s weak cultural orientation toward reading books, and the remaining 25 points are explained by the lower effectiveness of educational systems in teaching cognitive skills.